(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
These reflections treat the notion of “Justice” as a topic to stress the relationship between “theology” and “critical theory” in Max Horkheimer’s latest work. Eventhough he didn’t develop an specific work in regard to this issue, he empasises on it in several times turning it into one of the central points when time comes to wonder about “critical theory”. In regard to the author’s thesis, the theological turn of Horkheimer’s thinking will show the radicalization of his idea of “Justice” and, furthermore, it will help to draw some general insights for a radical politics.